Assessment of Antioxidant Activity of Spray Dried Extracts of Psidium guajava Leaves by DPPH and Chemiluminescence Inhibition in Human Neutrophils. (13th April 2014) - Fernandes, M. R. V.; Azzolini, A. E. C. S.; Martinez, M. L. L.; Souza, C. R. F.; Lucisano-Valim, Y. M.; Oliveira, W. P.
Abstract : This work evaluated the physicochemical properties and antioxidant activity of spray dried extracts (SDE) from Psidium guajava L. leaves. Different drying carriers, namely, maltodextrin, colloidal silicon dioxide, Arabic gum, and β -cyclodextrin at concentrations of 40 and 80% relative to solids content, were added to drying composition. SDE were characterized through determination of the total phenolic, tannins, and flavonoid content. Antioxidant potential of the SDE was assessed by two assays: cellular test that measures the luminol-enhanced chemiluminescence (LumCL) produced by neutrophils stimulated with phorbol myristate acetate (PMA) and the DPPH radical scavenging (DPPH* method). In both assays the antioxidant activity of the SDE occurred in a concentration-dependent manner and showed no toxicity to the cells. Using the CLlum method, the IC50 ranged from 5.42 to 6.50 µg/mL. The IC50 of the SDE ranged from 7.96 to 8.11 µg/mL using the DPPH method. Psidium guajava SDE presented significant antioxidant activity; thus they show high potential as an active phytopharmaceutical ingredient. Our findings in human neutrophils are pharmacologically relevant since they indicate that P. guajava SDE is a potential antioxidant and anti-inflammatory agent in human cells.